PENERAPAN MEDIA PAPAN BERPAKU UNTUK MENINGKATKAN HASIL BELAJAR GEOMETRI BANGUN DATAR DI KELAS II SD IT KAYYASAH KOTA LAMA - Mila Lestari (Dharmas Education Journal (DE_Journal), 2021)
In implementing Mathematics learning at SD IT Kayyasah Kota Lama it runs smoothly and well. This type of research is in the form of Classroom Action Research which consists of several stages, namely (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection, which lasts for two meetings in the implementation of Mathematics learning at SD IT Kayyasah Kota Lama runs smoothly and well. in cycle I learning uses thematic books and explains on the blackboard so that it makes students easily bored so that teachers must be good at making the class conducive and students can understand it. In the second cycle of learning using props, namely nail boards so that the teacher explains them through the media. The purpose of this study was to improve mathematics learning outcomes by using nailed board learning media in class II SD IT Kayyasah Kota Lama. The results of the research obtained in the first cycle showed that the completeness of the students reached a score of 12 with good categories and classical completeness of 71%. The results obtained in the second cycle, namely from the use of nailed board media obtained a score of 15 in the very good category and student learning outcomes increased with 88% classical completeness. Based on the research results, it can be stated that the use of nailed board media can improve the learning outcomes of class II students of SD IT Kayyasah Kota Lama.